Hypertension Management in Primary Care: A Cluster Randomized Trial of a Physician-focused Educational Intervention - Weltermann, Birgitta (Dtsch Arztebl Int, 2016)
BACKGROUND: To improve hypertension control, this cluster randomized trial evaluated the effectiveness of physician manager education about hypertension management. METHODS: After randomization at practice level, primary care physicians of the intervention arm, whose practices collaborated with a university department, participated in a three-session education on evidence-based hypertensiology and practice implementation strategies. The primary outcome was blood pressure (BP) control (ambulatory blood pressure [ABP] <130/80 mmHg) after 5 months. Secondary outcomes were changes in BP and practice routines regarding hypertension management. Following an intention-to-treat approach, data analyses included crude and adjusted generalized mixed models and sensitivity analyses. These took into account sex, age, ≥ hypertension-related disease and resistant hypertension (RH). RESULTS: The analysis included 103 of 169 patients from 22 practices. Overall, BP decrease was –8.2 systolic and –4.1 mmHg diastolic. The intervention had no effect on BP control (odds ratio 0.84 [95% CI 0.29–2.43]) and BP changes (interventional effect: systolic –2.48 mmHg [95% CI –7.24 to 2.29], diastolic –0.25 mmHg [95% CI 3.31 to 2.82]). Sensitivity analysis indicated effect modification in patients with RH. Intervention practices requested educational input on difficult cases, and newly implemented 3 practice strategies (14.5±2.6 versus 11.4±2.2; P=0.005). CONCLUSIONS: After the short follow-up of 5 months, the intervention had no impact on BP control but improved the use of practice strategies.